2016
DOI: 10.2147/ccide.s87837
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to find out the relationship between the inner inter-canthal distance, interpupillary distance, inter-commissural width, inter-alar width, and the width of maxillary anterior teeth in Aryans and Mongoloids

Abstract: Background One of the most confusing and difficult aspects of complete denture prosthodontics is the selection of appropriately sized maxillary anterior denture teeth. Various guidelines have been suggested for determining the size of anterior teeth, but different opinions have been reported regarding their significance. In the study reported here, the relationships between facial measurements and the width of maxillary anterior teeth in two ethnic groups, namely Aryans and Mongoloids, were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
(17 reference statements)
2
24
0
Order By: Relevance
“…Discussions on this topic are present in the contemporary professional literature. [20][21][22][23][24][25][26][27][28] Reviews of the recent scientific literature reveal studies Graph 1: Measurement of IAD in various population groups that were carried out using different methodology and sample size, different face and natural teeth parameters, 8,[10][11][12][13]15,19,20 casts, 5,[16][17][18]21,22 or photographs, 5,14,16,17,20 as well as various types of gauge which make the comparison of results very difficult. The authors here used a variety of instruments to determine the measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussions on this topic are present in the contemporary professional literature. [20][21][22][23][24][25][26][27][28] Reviews of the recent scientific literature reveal studies Graph 1: Measurement of IAD in various population groups that were carried out using different methodology and sample size, different face and natural teeth parameters, 8,[10][11][12][13]15,19,20 casts, 5,[16][17][18]21,22 or photographs, 5,14,16,17,20 as well as various types of gauge which make the comparison of results very difficult. The authors here used a variety of instruments to determine the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…9 When maxillary anterior teeth width was correlated with IAD, Indian population showed the highest correlation with IAD, mainly South Indian females with squareshaped arch (r = 0.52) 16 followed by North Indian females (r = 0.457), 14 and the least correlation was found in Asian population (r = 0.089), 21 whereas negative correlation was seen in Aryans (r = −0342) and Mangoloids (r = −0.217). 5 Facial proportions can vary in different ethnic groups. 13,28 South Indian population has the highest correlation with IAD, which could be due to Dravidian ethnic group.…”
Section: Graph 3: Measurement Of Ipd In Various Population Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…the use of inter-alar and intercommissural distance showed a good concordance with WCI 7 . Similarly, Mishra et al reported that inter-alar distance used to determine WCI is quite accurate when used in conjunction with in-tercommissural or interpupillary distance 8 . The maximum length of the ears was used in this study.…”
Section: Discussionmentioning
confidence: 96%
“…An important factor contributing to a harmonious dentition is size, shape and arrangement of maxillary central incisors seen from the front 5 . Different techniques have been proposed to optimize the harmonious shape of maxillary anterior teeth 1,[4][5][6][7][8] . These are based on the work of Levin, who introduced the golden ratio in dental aesthetics 9 .…”
Section: Introductionmentioning
confidence: 99%